STUDI EKSPERIMEN KUAT TEKAN BETON MENGGUNAKAN SEMEN PPC DENGAN TAMBAHAN ADDITON - Kiswandi, -; Mungok, Chrisna Djaja; Supriyadi, Asep (JeLAST : Jurnal PWK, Laut, Sipil, Tambang, 2018)
This paper presents the effect of the use of Additon h.e. of Portland Gresik's cement Portland Pozzoland Cement (PPC) concrete. Test specimens made cylindrical with size Ã˜ 15 cm height 30 cm. Determination of concrete mixture using ACI Modified method. The planned concrete quality is fc '= 22.5 Mpa. From the result of the research on Gresik cement, the normal concrete got the compressive strength of 29,624 MPa, while the concrete with additon variation of 80 cc obtained sebedsar 31,538 MPa, variation of additon 120 cc equal to 33,399 Mpa and concrete with additon 200 cc equal to 35,878 MPa. While the result of normal tensile strength of concrete, additon variation h.e 80 cc, 120 cc, and 200 cc respectively reached 3,276 Mpa; 3,630 Mpa; 3,889 Mpa; and 4,266 Mpa)Â Keywords: Additon H.E, Compressive strength, split tensile strength, PPC cement